Respuesta :
(X+3)-15=7(x-2)+8
X+3-15=7x-14+8
X-12=7x-6
-7x -7x
-6x-12=-6
12 12
-6x/-6 6/-6
Answer: x= -1
X+3-15=7x-14+8
X-12=7x-6
-7x -7x
-6x-12=-6
12 12
-6x/-6 6/-6
Answer: x= -1
Solve using BEDMAS
(x+3)-15=7(x-2)+8
x+3-15=7(x-2)+8
x-12=7(x-2)+8
Distribute the Brackets
x-12=7(x-2)+8
x-12=7x-14+8
x-12=7x-6
Add 12 to both sides.
(x-12)+12=(7x-6)+12
x=7x+6
Subtract 7x from both sides
(x)-7x=(7x+6)-7x
-6x=6
Divide both sides by -6
(-6x)/-6=(6)/-6
x= -1
Hope this helps!
-Benjamin
(x+3)-15=7(x-2)+8
x+3-15=7(x-2)+8
x-12=7(x-2)+8
Distribute the Brackets
x-12=7(x-2)+8
x-12=7x-14+8
x-12=7x-6
Add 12 to both sides.
(x-12)+12=(7x-6)+12
x=7x+6
Subtract 7x from both sides
(x)-7x=(7x+6)-7x
-6x=6
Divide both sides by -6
(-6x)/-6=(6)/-6
x= -1
Hope this helps!
-Benjamin